The Hair Cell α9α10 Nicotinic Acetylcholine Receptor: Odd Cousin in an Old Family - Marcela Lipovsek (Frontiers Media S.A., 2021)
Nicotinic acetylcholine receptors (nAChRs) are a subfamily of pentameric ligand-gated ion channels with members identified in most eumetazoan clades. In vertebrates, they are divided into three subgroups, according to their main tissue of expression: neuronal, muscle and hair cell nAChRs. Each receptor subtype is composed of different subunits, encoded by paralogous genes. The latest to be identified are the α9 and α10 subunits, expressed in the mechanosensory hair cells of the inner ear and the lateral line, where they mediate efferent modulation. α9α10 nAChRs are the most divergent amongst all nicotinic receptors, showing marked differences in their degree of sequence conservation, their expression pattern, their subunit co-assembly rules and, most importantly, their functional properties. Here, we review recent advances in the understanding of the structure and evolution of nAChRs. We discuss the functional consequences of sequence divergence and conservation, with special emphasis on the hair cell α9α10 receptor, a seemingly distant cousin of neuronal and muscle nicotinic receptors. Finally, we highlight potential links between the evolution of the octavolateral system and the extreme divergence of vertebrate α9α10 receptors.